Sexual Violence at University Level: A Philosophical Feminism Overview - Widiantini, Ikhaputri (Yayasan Jurnal Perempuan, 2021)
This paper highlights the philosophical issues related to sexual violence cases at the university level. Many reports were found related to the sexual violence cases at the university level, but did not came to a solution that take sides to the victim. This is not just a problem about the unstrict law to handle the cases. There is a basic problem that underline in the mindset and behavior. Rape culture in society failed us to understand that this is a form of violence against humanity. The basis of patriarchal logic also affirms the condition. Based on the standpoint feminism method, also supported by data on sexual violence reports, I pointed the importance of using the feminist logic approach in viewing this issue. I aim to restore the point of view on siding the victim which can provide justice in handling the sexual violence cases at the university level.